(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The article analyzes the socio-philosophical significance of media information systems in improving educational culture. In the process of developing educational culture, the mechanisms of modern formation of knowledge exchange, spiritual values, and communicative relations between man and society are highlighted. Media are considered not only a technological opportunity for the field of education, but also a social phenomenon that instills the philosophical content of information, enlightenment, and culture into the consciousness of the general public. The creation of the possibility of rapid transmission of scientific innovations, methodologies, and innovative ideas related to education through these systems is justified, as well as the role of a person in the formation of consciousness and the adaptation of new knowledge to the new knowledge. Media information systems are interpreted as a means of directing a person to independent thinking, active intellectual search, and interactive communication in the educational process. The article shows that, in general, the improvement of educational culture is inextricably linked with the spiritual and educational development of society, and the integration of media information systems in this process is an important factor from a socio-philosophical point of view.